Inferring Chemogenomic Features from Drug‐Target Interaction Networks. Issue 11 (10th December 2013) - Yamanishi, Yoshihiro
Abstract Drug effects are mainly caused by the interactions between drug molecules and target proteins including primary targets and off‐targets. Understanding of the molecular mechanisms behind overall drugtarget interactions is crucial in the drug design process. In this paper we review recently developed methods to infer chemogenomic features (the underlying associations between drug chemical substructures and protein domains) which are strongly involved in drug‐target interaction networks. We show the usefulness of the methods to detect ligand chemical fragments specific for each protein domain and ligand core substructures important for a wide range of protein families. We also discuss how to use the chemogenomic features for predicting unknown drug‐target interactions on a large scale.